Assessment of Physical Fitness and Body Mass Index (BMI) of (6-9) Years in Jerash City - Al-Khazaleh, Wasfi Mohammad; Hrahahsheh , Laiali Alayan (Dirasat: Educational Sciences, 2020)
This Study aims to assess fitness test and body mass index (BMI) of (6-9) years at Jerash schools. The researchers used a descriptive methodology on a sample of (1114) students from Al-Nasseem district schools. Eight schools were chosen randomly out of (17) schools. The students were distributed into two groups: (401) males and (713) females. The study included the measures of Munich physical fitness test. The findings showed that there is a shortness in power, endurance, and coordination ability, and a natural level of accuracy and flexibility for both males and females among the age of (6). In addition, the findings for the age of (7) showed shortness in coordination and muscular power. The findings of accuracy and muscular endurance were normal for both males and females, but at age of (8) the findings revealed a natural level among males in all tests except the muscular power to test which was in shortness level. The findings revealed normal levels among both males and females in all tests except the flexibility test which revealed shortness for females.